2018
DOI: 10.1108/ccij-04-2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

Vigilant resilience: the possibilities for renewal through preparedness

Abstract: Purpose Post-crisis renewal discourse (Ulmer et al., 2007) is one form of communication that stakeholders may use as they attempt to organize for resilience. The purpose of this paper propose extending Discourse of Renewal Theory to explain how it could enact a different kind of resilience than scholars typically consider. Organizational resilience strategies often focus on the recovery or prevention stages of crisis management. Under conditions of persistent threat, it would be more productive for renewal dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Discourse of Renewal deemphasizes the role of image in a crisis and instead centers on how organizations or communities can learn from crises, communicate consistently using their values, constitute prospective visions of transformation and recovery, and emphasize optimism and commitment to recovery following negative events (Ulmer et al, 2019). Over the past 20 years, scholars have extensively examined renewal in a wide variety of organizational and community crises (Carlson, 2018; Herovic & Veil, 2015; Littlefield, Reierson, Cowden, Stowman, & Feather, 2009; Paquette, 2015; Reierson & Littlefield, 2012; Sellnow, Iverson, & Sellnow, 2017). Organizational learning, ethical communication, prospective vision, and effective organizational rhetoric are ways that organizations can effectively manage a crisis.…”
Section: Discourse Of Renewal Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Discourse of Renewal deemphasizes the role of image in a crisis and instead centers on how organizations or communities can learn from crises, communicate consistently using their values, constitute prospective visions of transformation and recovery, and emphasize optimism and commitment to recovery following negative events (Ulmer et al, 2019). Over the past 20 years, scholars have extensively examined renewal in a wide variety of organizational and community crises (Carlson, 2018; Herovic & Veil, 2015; Littlefield, Reierson, Cowden, Stowman, & Feather, 2009; Paquette, 2015; Reierson & Littlefield, 2012; Sellnow, Iverson, & Sellnow, 2017). Organizational learning, ethical communication, prospective vision, and effective organizational rhetoric are ways that organizations can effectively manage a crisis.…”
Section: Discourse Of Renewal Theorymentioning
confidence: 99%
“…The conditions for renewal are affected by communication practices before a crisis occurs (Ulmer, 2001). Moreover, recent research has begun to advance the point that organizations should incorporate preparedness into their Discourse of Renewal (Carlson, 2018). To put recommendations from the theory into practice, organizations must meet certain preconditions.…”
Section: Measurement Of Readiness For Renewal In the Precrisis Stagementioning
confidence: 99%
“… System Petrochemical plant Resilience as an outcome Resilience promoting safety Bento and Garotti (2019) Conceptual A network analytic approach to resilience challenges brought changes in workplace demographics. System Production andIntegrated operations Resilience capabilities Not about safety Carlson (2018) Empirical Qualitative Renewal discourse in post-crisis communication and emphasis on preparedness facilitates dialogues about interdependencies among stakeholders. System Oil Spill Recovery Resilience capabilities Not about safety Gomes et al 2009 Empirical Qualitative Resilience as an emergent property related to variability at different levels.…”
Section: Resultsmentioning
confidence: 99%
“…Bearing that in mind, it is possible to enquire if the evolutionary perspective informs the understanding of resilience in the selected literature of this scoping review. In response to this question, it is observed that although some articles (n = 6) ( Bento and Garotti, 2019 , Carlson, 2018 , Grabowski and Roberts, 2016 , Johnsen, 2012 ; Skjerve et al, 2012; Tveiten et al, 2012 ) make reference to adaptive processes, there is little in terms of articulating or investigating evolutionary processes related to resilience. The literature assumes in different forms a normative perspective towards resilience by focusing on indicators of resilience such as commitment, awareness and preparedness.…”
Section: Discussionmentioning
confidence: 99%
“…Also, resilience is the capability of a system to adjust its functionality during a disturbance or perturbation (Sarwar, Khan, Abimbola & James, 2018). According to Carlson (2018) organizational resilience strategies often focus on the recovery or prevention stages of crisis management. Under conditions of persistent threat, it would be more productive for renewal discourse to emphasize greater preparedness.…”
Section: Strategic Resiliencementioning
confidence: 99%